Examining the Role of Video-Recorded Speaking Task in Enhancing Students’ Oral Productive Skill - Siti Nurul Azkiya; Rahmi Rahayu (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2018)
ABSTRACTThe teaching of speaking in Indonesian schools faces some problems such as limited amount of practice and feedback and students’ anxiety. Addressing this issue, therefore, this study was aimed at examining the role of video-recorded speaking task in improving students’ oral productive skill measured through a speaking test and understand students’ response on the use of the task through a questionnaire. It was a quasi-experimental study, the sample of which was 87 tenth grade students of one senior high selected through a purposive sampling technique and randomly assigned into experimental and controlled classes. The test served as a pretest administered at the beginning and as a posttest distributed at the end of the treatment, which data were analyzed using t-test. The effectiveness of the treatment was analyzed from the posttest and gained scores, which findings revealed higher achievements of the experimental group. In addition, students were happy to do this task. These findings mean that video-recorded speaking task play roles in enhancing students’ oral productive skill and support previous studies on the effectiveness of video-recorded speaking tasks. ABSTRAKPengajaran berbicara di banyak sekolah di Indonesia menghadapi berbagai masalah, diantaranya terbatasnya waktu untuk praktik keterampilan berbicara dan feedback oleh guru serta keengganan siswa untuk berlatih. Untuk menjawab tantangan, studi ini ditujukan untuk menguji peran tugas berbicara yang divideokan dan pendapat siswa terhadap diberlakukannya tugas ini. Studi ini menggunakan desain kuasi-experiment dengan purposive sampling yang kemudian secara acak dibagi menjadi kelas eksperimen dan kelas kontrol. Tes dilakukan 2 kali sebagai pretest dan posttest, di mana data posttest dan gain score dianalisis menggunaan uji t-test. Hasil analisis menunjukkan bahwa nilai keterampilan berbicara kelas eksperimen secara signifikan lebih tinggi. Selain itu, siswa juga senang mengerjakan tugas ini. Temuan ini menunjukkan bahwa pemberian tugas berbicara dengan divideokan bisa meningkatkan kemampuan produktif secara oral dan mendukung temuan terdahulu terkait efektifitas tugas berbicara yang divideokan. How to Cite: Azkiyah, S. N., Rahayu, R. (2018). Examining the Role of Video-Recorded Speaking Task in Enhancing Students’ Oral Productive Skill. IJEE (Indonesian Journal of English Education), 5(2), 204-218. doi:10.15408/ijee.v5i2.11193.